Flight to Quality or to Captivity : Information and Credit Allocation - Dell'Ariccia, Giovanni (IMF Working Papers; Working Paper ;, 2001)
Superior information exchanged over the course of lending relationships generates bank-client specificities to the extent that such information cannot be communicated credibly to outsiders. Consequently, banks obtain higher profits from more captured borrowers than from borrowers with financing alternatives. We refer to this as a 'flight to captivity' effect. Negative shocks, associated with monetary contractions or foreign entry, cause a reallocation of bank credit away from more transparent borrowers and toward more opaque, more captured borrowers. The paper applies these ideas to the analysis of bank behavior in transition economies after financial liberalization and monetary policy contractions.